Evaluation of Giardia lamblia thioredoxin reductase as drug activating enzyme and as drug target. Issue 3 (December 2016) - Leitsch, David; Müller, Joachim; Müller, Norbert
Abstract: The antioxidative enzyme thioredoxin reductase (TrxR) has been suggested to be a drug target in several pathogens, including the protist parasite Giardia lamblia . TrxR is also believed to catalyse the reduction of nitro drugs, e . g . metronidazole and furazolidone, a reaction required to render these compounds toxic to G . lamblia and other microaerophiles/anaerobes. It was the objective of this study to assess the potential of TrxR as a drug target in G . lamblia and to find direct evidence for the role of this enzyme in the activation of metronidazole and other nitro drugs. TrxR was overexpressed approximately 10-fold in G . lamblia WB C6 cells by placing the trxR gene behind the arginine deiminase (ADI) promoter on a plasmid. Likewise, a mutant TrxR with a defective disulphide reductase catalytic site was strongly expressed in another G . lamblia WB C6 cell line. Susceptibilities to five antigiardial drugs, i . e . metronidazole, furazolidone, nitazoxanide, albendazole and auranofin were determined in both transfectant cell lines and compared to wildtype. Further, the impact of all five drugs on TrxR activity in vivo was measured. Overexpression of TrxR rendered G . lamblia WB C6 more susceptible to metronidazole and furazolidone but not to nitazoxanide, albendazole, and auranofin. Of all five drugs tested, only auranofin had an appreciably negative effect on TrxR activity in vivo, albeit to a much smaller extent than expected. Overexpression of TrxR and mutant TrxR had hardly any impact on growth of G . lamblia WB C6, although the enzyme also exerts a strong NADPH oxidase activity which is a source of oxidative stress. Our results constitute first direct evidence for the notion that TrxR is an activator of metronidazole and furazolidone but rather question that it is a relevant drug target of presently used antigiardial drugs. Graphical abstract: Highlights: Thioredoxin reductase can be overexpressed in Giardia lamblia more than tenfold. Thioredoxin reductase is an activator of metronidazole and furazolidone. Thioredoxin is not an important target of presently used antigiardial drugs.